PERANCANGAN SISTEM PENGADUAN MASYARAKAT DI DESA KERTABASUKI - Sunengsih, Ayu; Abdurahman, Dede (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Public services are an obligation of the village government to fulfill the needs of the community in accordance with laws and regulations. One form of service is community complaints that function as a means of conveying complaints and aspirations of citizens. In Kertabasuki Village, Majalengka Regency, the complaint mechanism is still carried out manually through face-to-face, telephone, and short messages, so the follow-up of complaints is not optimal. Data from mid-2023 to 2024 recorded 50 reports of street lighting, 7 losses, 2 floods, and around 100 related to social assistance. This condition shows the need to utilize technology to improve service effectiveness. A community complaint website is a relevant solution because it facilitates recording, tracking, and monitoring the status of reports, and supports village government transparency and responsiveness.